Discovery of Novel Circulating Immune Complexes in Lupus Nephritis Using Immunoproteomics - Tang, Chenling; Fang, Min; Tan, Gongjun; Zhang, Shu; Yang, Bowen; Li, Yaxi; Zhang, Ting; Saxena, Ramesh; Mohan, Chandra; Wu, Tianfu (Frontiers in Immunology, 2022)
Objective The goal is to discover novel circulating immune complexes (ICx) in the serum of Lupus Nephritis (LN) as potential biomarkers. Methods Protein A/G magnetic beads or C1q-coated plates were used to capture ICx in the serum of LN, followed by the identification of immunoglobulin-binding proteins using liquid chromatography and tandem mass spectrometry (LC-MS/MS). Bioinformatic approaches and single-cell RNA sequencing (scRNA Seq) databases were used to select potential candidate ICx markers in LN. The selected ICx markers were further validated using ELISA. Results A total of 300 immunoglobulin-binding proteins were discovered in the screening, among which 77 proteins were detectable only in LN samples. Bioinformatics-assisted selection allowed us to further identify 10 potential immunoglobulin-binding proteins, which form ICx as potential biomarkers in LN. In a validation cohort of 62 LN patients and 21 healthy controls (HC), we found prolyl 3-hydroxylase 1 (P3H1), phosphatase and actin regulator 4 (PHACTR4) and regulator of G-protein signaling 12 (RGS12) ICx exhibited discriminative capability in distinguishing LN from HC, with an area under the curve (AUC) values of 0.82, 0.99 and 0.90, respectively. Furthermore, a biomarker panel comprised of CD14, CD34, cystatin A, myocyte enhancer factor 2C (MEF2C), RGS12 and ubiquitin C (UBC) ICx could distinguish active LN from inactive LN with an AUC value of 0.85, which is comparable to or better than pathological parameters such as renal activity index (AI) and renal chronicity index (CI). Conclusion Immunoproteomics-based discovery studies have enabled us to identify circulating immune complexes as potential biomarkers of LN.